Brain blood vessel autoantibodies in patients with NMDA and GABAA receptor encephalitis: identification of unconventional Myosin-X as target antigen - Li, Lucie Y.; Kreye, Jakob; Burek, Malgorzata; Cordero-Gomez, César; Barthel, Paula C.; Sánchez-Sendín, Elisa; Kornau, Hans-Christian; Schmitz, Dietmar; Scharf, Madeleine; Meybohm, Patrick; Reincke, S. Momsen; Prüss, Harald; et al. (Frontiers in Cellular Neuroscience, 2023)
The antibody repertoire from CSF-derived antibody-secreting cells and memory B-cells in pa-tients with encephalitis contains a considerable number of antibodies that do not target the dis-ease-defining autoantigen such as the GABA or NMDA receptors. This study focuses on the functional relevance of autoantibodies to brain blood vessels in patients with GABAA and NMDA receptor encephalitis. We tested 149 human monoclonal IgG antibodies from the cere-brospinal fluid of six patients with different forms of autoimmune encephalitis on murine brain sections for reactivity to blood vessels using immunohistochemistry. Positive candidates were tested for reactivity with purified brain blood vessels, effects on transendothelial electrical re-sistance (TEER) and expression of tight junction proteins as well as gene regulation using human brain microvascular endothelial hCMEC/D3 cells as in vitro blood-brain barrier model. One blood-vessel reactive antibody was infused intrathecally by pump injection in mice to study in vivo binding and effects on tight junction proteins such as Occludin. Target protein identification was addressed using transfected HEK293 cells. Six antibodies reacted with brain blood vessels, three were from the same patient with GABAAR encephalitis, the other three were from different patients with NMDAR encephalitis. One antibody from a NMDAR encephalitis patient, mAb 011-138, also reacted with cerebellar Purkinje cells. In this case, treatment of hCMEC/D3 cells resulted in decreased TEER, reduced Occludin expression and mRNA levels. Functional relevance in vivo was confirmed as Occludin downregulation was observed in mAb 011-138-infused animals. Unconventional Myosin-X was identified as a novel autoimmune target for this antibody. We conclude that autoantibodies to blood vessels occur in autoimmune encephalitis patients and might contribute to a disruption of the blood-brain barrier thereby suggesting a potential pathophysiological relevance of these antibodies.